Mechanical properties of solid oxide fuel cell glass-ceramic sealants in the system BaO/SrO-MgO-B2O3-SiO2. Issue 11 (September 2017) - Rodríguez-López, S.; Wei, J.; Laurenti, K.C.; Mathias, I.; Justo, V.M.; Serbena, F.C.; Baudín, C.; Malzbender, J.; Pascual, M.J.
Abstract: Planar solid oxide fuel cells (p-SOFCs) require materials that can satisfy the high mechanical demands related to their utilization in stationary and, especially, in mobile applications. Two suitable glass-ceramic sealants based on the system BaO/SrO-MgO-B2 O3 -SiO2 have been characterized with respect to their mechanical properties such as hardness, Young's modulus, flexural strength at room and elevated temperature, fracture toughness as well as creep behavior at relevant operation temperatures (800 °C). Fracture toughness was calculated from crack opening displacements (COD) and the results were compared with fracture toughness measured by bending tests of notched bar samples. The mechanical behavior has been discussed regarding different thermal aging times of the glass-ceramics and their microstructural evolution. The glass-ceramics containing SrO revealed a better mechanical behavior than glass-ceramics with BaO. In particular, several superior properties were found in comparison to previously reported materials for this application.